2019
DOI: 10.1016/j.jaci.2018.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet on the childhood gut microbiome and its implications for atopic dermatitis

Abstract: Effects of diet on the childhood gut microbiome and its implications for atopic dermatitisTo the Editor:Atopic dermatitis (AD) is a common childhood disorder with significant reductions in the child's quality of life. The composition and diversity of the early gut microbiota has been linked to the development of atopic conditions including AD. 1 Although the prevalence of atopic diseases is lower in Africa, 2 individuals of African origin who live in Western countries are at a significantly higher risk for ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 13 publications
2
31
0
Order By: Relevance
“…Amasi is a fermented milk rich in probiotics, which might contribute to gut microbial diversity, possibly compensating for deficient gut microbial diversity, which can be present in urban children. 36…”
Section: Unpasteurized Milk and Amasi (Fermented Milk)mentioning
confidence: 99%
See 2 more Smart Citations
“…Amasi is a fermented milk rich in probiotics, which might contribute to gut microbial diversity, possibly compensating for deficient gut microbial diversity, which can be present in urban children. 36…”
Section: Unpasteurized Milk and Amasi (Fermented Milk)mentioning
confidence: 99%
“…A subsection of the rural cohort (47 children) were included as nonatopic control subjects in a study 36,47 comparing the diet and intestinal microbiome in black African children with and without AD. Significantly lower sugar and saturated fat consumption was reported in the diets of rural children without AD than in their atopic counterparts, and a significant association was found between higher consumption of sugar and AD.…”
Section: Ages and Fruit And Vegetable Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also noted that a butyrate‐rich diet (enriched in fibre‐rich foods and milk fat) shaped the gut microbiome and reduced AD incidence . A recent study in South African children demonstrated differences in gut microbiome composition between rural children with AD compared with their healthy counterparts …”
Section: Summary Of the Major Issues Concerning Ad In Saamentioning
confidence: 93%
“…27 A recent study in South African children demonstrated differences in gut microbiome composition between rural children with AD compared with their healthy counterparts. 28 Recent reports have indicated a multipolarity of immune axes in AD. Notably, Asian AD skin phenotypes included psoriatic features that were associated with a strong Th17 immune axis.…”
Section: Genetic Risk Mechanisms and Environmental Effectsmentioning
confidence: 99%